Lignin-Based Electrospun Carbon Nanofibers - Manish Kumar (Frontiers in Materials, 2019)
The article summarizes the scientific progress that has occurred in the past several years in regard to the preparation of carbon nanofibers from lignin as a low-cost environmentally-friendly raw material using electrospinning. It presents an overview of using lignin, electrospinning, and carbonization to convert lignin to carbon nanofibers. Lignin is a renewable source for carbon material, and it is very abundant in nature. It is mostly produced as a byproduct from the paper industry and biomass fractionation. Despite its extensive availability and beneficial properties, only a few studies have reported on its use in electronic applications. Lignin-based carbon nanofibers have a high surface area, high porosity, and good electrical conductivity; thus, it is proposed that they are suitable for future energy storage applications.